A novel scheduling algorithm for data-intensive workflow in virtualised clouds. (14th June 2019) - Li, Feng
In cloud platforms, workflow applications have been widely used to solve the complicated problems, which often need to process a large volume of data. However, the characteristic of data-intensive for these applications are easily to result in low execution efficiency due to networking traffic or congestion. In this paper, we present a workflow scheduling algorithm which is capable of minimising the cost of networking communication and therefore improving the execution efficiency of those workflow applications. Extensive experiments are conducted on some real-world workflows to examine the performance of the proposed algorithm, and the results show that it can significantly reduce the communication cost and improve the execution efficiency of data-intensive workflows comparing with existing algorithms.